Measuring business value and sustainability performance - Ferguson, David (Cranfield University School of Management, 2009)
The integration of corporate sustainability within operations remains an important and fundamental challenge for business. This paper first consolidates and then builds upon the EABIS-supported activities of Cranfield School of Management with business practitioners. It focuses on the performance and evaluation criteria relating to determining corporate responsibility (CR) value. The paper begins by categorising components of CR in terms of decision-making levels and business case requirements. It then describes a methodology for establishing CR issues with the prioritisation of stakeholders before linking this relationship onto business benefits and shareholder value drivers. Using illustrated models and worked examples, sections within the paper provide further practical advice and guidance for developing and populating elements within the framework. Additional sections then complement the application of the CR Value-chain framework, with a chapter on performance measurement that explores the key performance measure characteristics required to underpin the performance element of the framework. The final chapter describes decision-making support tools, such as financial appraisals and risk evaluations, which also underpin the shareholder value approach and should be integrated within this corporate sustainability value management framework. A key purpose of this approach is to support the integration of sustainability performance management processes and systems within business practice. It explores methods for making more explicit the issues surrounding CR and financial value. It also provides useful approaches for helping businesses select, measure and evaluate performance for internal CR strategies, policies and processes. Some analytical methods are considered for identifying the costs and benefits from sustainability-related issues, projects and new ventures, including discussions with regard to harmonising existing business functions. This paper serves to provide an early prototype for future approaches towards integrated sustainability performance management systems.